Ion acceleration and plasma jet formation in ultra-thin foils undergoing expansion and relativistic transparency - King,M; Gray,RJ; Powell,HW; MacLellan,DA; Gonzalez-Izquierdo,B; Stockhausen,LC; Hicks,GS; Dover,NP; Rusby,DR; Carroll,DC; Padda,H; Torres,R; et al. (Elsevier, 2016)
At sufficiently high laser intensities, the rapid heating to relativistic velocities and resulting decompression of plasma electrons in an ultra-thin target foil can result in the target becoming relativistically transparent to the laser light during the interaction. Ion acceleration in this regime is strongly affected by the transition from an opaque to a relativistically transparent plasma. By spatially resolving the laser-accelerated proton beam at near-normal laser incidence and at an incidence angle of 30°, we identify characteristic features both experimentally and in particle-in-cell simulations which are consistent with the onset of three distinct ion acceleration mechanisms: sheath acceleration; radiation pressure acceleration; and transparency-enhanced acceleration. The latter mechanism occurs late in the interaction and is mediated by the formation of a plasma jet extending into the expanding ion population. The effect of laser incident angle on the plasma jet is explored.